Three-year follow-up of posterior chamber toric phakic intraocular lens implantation for the correction of high myopic astigmatism in eyes with keratoconus. Issue 2 (21st August 2014) - Kamiya, Kazutaka; Shimizu, Kimiya; Kobashi, Hidenaga; Igarashi, Akihito; Komatsu, Mari; Nakamura, Akio; Kojima, Takashi; Nakamura, Tomoaki
Abstract : Aim: To assess the clinical outcomes following the use of toric implantable collamer lenses (toric ICL, STAAR Surgical) for the correction of high myopic astigmatism with keratoconus. Methods: This retrospective study evaluated 21 eyes of 11 patients with spherical equivalents of −9.70±2.33 D (mean±SD) and astigmatism of −3.21±1.56 D who underwent toric ICL implantation for keratoconus. Preoperatively, and at 1, 3 and 6 months and 1, 2 and 3 years postoperatively, we assessed the safety, efficacy, predictability, stability and adverse events of the surgery. Results: The logarithm of the minimum angle of resolution (logMAR) uncorrected distance visual acuity (UDVA) and the logMAR corrected distance visual acuity (CDVA) were −0.06±0.11 and −0.12±0.09, respectively, at 3 years postoperatively. At 3 years, 67% and 86% of the eyes were within ±0.5 and ±1.0 D, respectively, of the targeted correction. Manifest refraction changes of 0.04±0.33 D occurred from 1 month to 3 years postoperatively. No significant change in manifest refraction (analysis of variance, p=0.989) or keratometry (p=0.951), or vision-threatening complications occurred during the observation period. Conclusions: Toric ICL implantation is beneficial according to measures of safety, efficacy, predictability and stability for the correction of refractive errors for keratoconus during a 3-year observation period. The disease did not progress even in the late-postoperative period, suggesting the viability of this procedure as a surgical option for the treatment of such eyes.